Assessing inflation vulnerability an early warning system for inflation in the Philippines. - Cruz, Christopher John F. (University of the Philippines, 2013)
Abstract (With the adoptation of the Bangko Sentral ng Pilipinas (BSP) of the Inflation Targeting (IT) framework in 2002, average inflation went down in the past decasde from historical average but the BSP's inflation targets were breached 7 times since 2002. Against this backdrop, this paper attempts to develop early warning system (EWS) models for predicting the occurrence of high inflation in the Philippines. The models could complement the BSP's existing toolkit to assess the inflation environment as well as the risks to the inflation outlook. This paper employs two techniques, the policy-based technique (via Markov-switching models) to identify episodes of high and low inflation. Using the outcomes of the regime classification, logistic regression models are then estimated with the objective of quantifying the possibility of the occurrence of high inflation episodes. Empirical results show that the EWS models have some potential as a complementary tool in the BSP's monetary policy formulation based on their in-sample and out-of sample forecasting performance).